Making marijuana an environmental issue: Prohibition, pollution, and policy. (June 2019) - Polson, Michael
Over the past two decades, activists and market actors have successfully liberalized marijuana consumption and distribution in most US states. Given ongoing federal supply-side interdiction strategies, however, production has been another matter. This article traces the emergence of marijuana cultivation as an environmental matter. "The environment" increasingly constitutes a material-discursive social field into which actors (e.g. activists, law enforcement, producers, conservationists) can launch interventions into productive processes. The article traces three early, formative interventions in northern California: by federal agents to "reclaim" and protect public lands; by a county government to discipline and segregate compliant environmental citizens from recalcitrant, racialized "criminals"; and by producers themselves to mobilize environmental discourses in regulatory debates. Amidst ideas of pollution, reclamation, stewardship, and sustainability, these projects revalorized marijuana production, articulating with and departing from entrenched systems of inequality and stigma. As marijuana production liberalizes, this article draws attention to the legacy of prohibition moralities in regulatory debates, the necessity of incorporating criminalized actors in civil regulation and knowledge formation, and the possibility for a liberation environmentality that exceeds the terms of exploitative, extractive relations that dominate contemporary agriculture, land use, and drug policy.